SOME LEGAL ASPECTS OF ELECTRONIC TRADE - Uzelac, Ozren; Protić, Dušan (Law - Theory and Practice, 2011)
Information technology today represents unavoidable factor and a highly developed part of social life. Without information technology and internet, today it is impossible to imagine any kind of serious business and connection with business partners. Advantages of this kind of business are enormous and mostly are concerning speed of taking actions, possibilities of easy contact with potential business partners all around the world, as well as university of communications and interaction. On the other hand, there are certain disadvantages as lack of information about potential client, his business credibility and capacity to conclude a job, as well as forming a valid legal frame for a legal job (substantive law and procedural law). In any case, Republic of Serbia with its positive legislation has entered these processes and begun to legally regulate this field.